2017
DOI: 10.1159/000484564
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Hepatocellular Carcinoma Aggressiveness Factors in Turkish Patients

Abstract: A large cohort of hepatocellular carcinoma (HCC) patients from several collaborating Turkish institutions were examined for the tumor parameters of maximum diameter (MTD), portal vein thrombosis (PVT), and α-fetoprotein (AFP) levels. A relationship was found between MTD and blood platelet levels. Patients with large ≥5 cm tumors who had normal platelet levels had significantly larger tumors, higher percent of PVT, and significantly lower blood total bilirubin and liver cirrhosis than similar ≥5 cm tumor patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
34
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(40 citation statements)
references
References 14 publications
5
34
1
Order By: Relevance
“…In this context, we addressed in this work the possible mechanisms that might underlie the prognostic usefulness of CRP, PLR and NLR. A working hypothesis that we have tested here, is that each or any of CRP, PLR or NLR might be related to indices of tumour aggressiveness, namely MTD, AFP, PVT and multifocality, as an explanation of their prognostic ability [30,36,37]. We found CRP was significantly related to MTD, AFP and PVT, and the Glasgow Index to MTD and AFP.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…In this context, we addressed in this work the possible mechanisms that might underlie the prognostic usefulness of CRP, PLR and NLR. A working hypothesis that we have tested here, is that each or any of CRP, PLR or NLR might be related to indices of tumour aggressiveness, namely MTD, AFP, PVT and multifocality, as an explanation of their prognostic ability [30,36,37]. We found CRP was significantly related to MTD, AFP and PVT, and the Glasgow Index to MTD and AFP.…”
Section: Discussionmentioning
confidence: 74%
“…Diagnosis was made either through tumour biopsy or according to international guidelines. Database management conformed to legislation on privacy and this study conforms to the ethical guidelines of the Declaration of Helsinki and approval for this retrospective study on de-identified HCC patients was obtained by the Institutional Review Board of each participating institution [30].…”
Section: Methodsmentioning
confidence: 99%
“…This is because the male/female ratio of viral hepatitis is higher in Turkey compared to other countries [13]. Because HBV infection is endemic in Turkey, the incidence of HBV was higher in our sample with HCCs compared to the literature; the causative agent was detected as HBV in 24 patients (77.4%) and HCV in seven (22.6%) [14].…”
Section: Discussionmentioning
confidence: 53%
“…However, there is also evidence stemming from clinical studies showing that the presence of thrombocytosis rather than thrombocytopenia may be associated with worse prognosis in patients with HCC, and that, in these patients, the presence of increased platelet count can be considered a marker of enhanced tumor aggressiveness and poorer survival [87,88,89,90]. More in detail, thrombocytosis is associated with greater tumor burden and more biological aggressiveness in patients with HCC [87,88,89,90]. Moreover, other studies have shown that an elevated pretreatment platelet count is associated with a higher risk of extra-hepatic spread in patients with early and very early HCC (HR = 2.12, 95%CI = 1.67–2.70), showing a diagnostic ability even superior in respect to AFP [72,73].…”
Section: The Specific Role Of Platelets In the Diagnosis And Prognmentioning
confidence: 99%